MANP Activation Of The cGMP Inhibits Aldosterone Via PDE2 And CYP11B2 In H295R Cells And In Mice. Issue 8 (8th June 2022) - Chen, Yang; Iyer, Seethalakshmi R.; Nikolaev, Viacheslav O.; Naro, Fabio; Pellegrini, Manuela; Cardarelli, Silvia; Ma, Xiao; Lee, Hon-Chi; Burnett, John C.
Abstract : Background: Aldosterone is a critical pathological driver for cardiac and renal diseases. We recently discovered that mutant atrial natriuretic peptide (MANP), a novel atrial natriuretic peptide (ANP) analog, possessed more potent aldosterone inhibitory action than ANP in vivo. MANP and natriuretic peptide (NP)-augmenting therapy sacubitril/valsartan are under investigations for human hypertension treatment. Understanding the elusive mechanism of aldosterone inhibition by NPs remains to be a priority. Conflicting results were reported on the roles of the pGC-A (particulate guanylyl cyclase A receptor) and NP clearance receptor in aldosterone inhibition. Furthermore, the function of PKG (protein kinase G) and PDEs (phosphodiesterases) on aldosterone regulation are not clear. Methods: In the present study, we investigated the molecular mechanism of aldosterone regulation in a human adrenocortical cell line H295R and in mice. Results: We first provided evidence to show that pGC-A, not NP clearance receptor, mediates aldosterone inhibition. Next, we confirmed that MANP inhibits aldosterone via PDE2 (phosphodiesterase 2) not PKG, with specific agonists, antagonists, siRNA silencing, and fluorescence resonance energy transfer experiments. Further, the inhibitory effect is mediated by a reduction of intracellular Ca2+ levels. We then illustrated that MANP directly reduces aldosterone synthase CYP11B2 (cytochrome p450 family 11 subfamily b member 2) expression via PDE2. Last, in PDE2 knockout mice, consistent with in vitro findings, embryonic adrenal CYP11B2 is markedly increased. Conclusions: Our results innovatively explore and expand the NP/pGC-A/3', 5', cyclic guanosine monophosphate (cGMP)/PDE2 pathway for aldosterone inhibition by MANP in vitro and in vivo. In addition, our data also support the development of MANP as a novel ANP analog drug for aldosterone excess treatment.